2016
DOI: 10.5812/traumamon.25304
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Self-Inflicted Stab Wounds Versus Assault-Induced Stab Wounds

Abstract: Background: Although self-inflicted and assault-induced knife injuries might have different mortality and morbidity rates, no studies have actually evaluated the importance of the cause of knife injuries in terms of patient outcomes and treatment strategies. Objectives: The aims of this study were to assess the difference between the outcomes of patients presenting with self-inflicted stab wounds (SISW) versus assault-induced stab wounds (AISW). Patients and Methods:A retrospective review of the relevant elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
(29 reference statements)
2
4
0
Order By: Relevance
“…Moreover, home was the most common place of injury, similar to the observation in Korea, Romania, UK, and USA. 5 , 8 , 17 , 24 Similar findings were reported in a community-based survey that involved 27 Egyptian governorates and included all injuries not only KRIs. 25 The most observed injury site was an isolated area in the chest, which was also observed in recent studies in Korea, Italy and USA.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Moreover, home was the most common place of injury, similar to the observation in Korea, Romania, UK, and USA. 5 , 8 , 17 , 24 Similar findings were reported in a community-based survey that involved 27 Egyptian governorates and included all injuries not only KRIs. 25 The most observed injury site was an isolated area in the chest, which was also observed in recent studies in Korea, Italy and USA.…”
Section: Discussionsupporting
confidence: 74%
“… 4 , 13 Moreover, the duration of hospital stay among our patients was similar with those in studies that were conducted in Korea and USA. 8 , 17 , 26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A smaller data set from South Korea also reported 50 per cent of abdominal stab wounds being SISWs. 3 The results from these studies support the significant association between psychiatric illness and SISWs. Although this study is a comprehensive representation of stab wounds at an urban Level I trauma center, it does have several limitations.…”
Section: Discussionsupporting
confidence: 60%
“…1 Previous work assessing patterns of SISWs demonstrated that victims of such wounds tended to be male, of older age, and have preexisting behavioral disorders. 3 Indeed, a substantial fraction of these patients have suicidal ideations and require inpatient or outpatient psychiatric therapy. 4 These patterns seem to stand in stark contrast to victims of assault stab wounds (ASWs), who constitute most of the stab wound victims at major trauma centers.…”
mentioning
confidence: 99%